From the positive to the regulatory state: Causes and consequences of changes in the mode of governance: with the introduction of Bob Jessop - Majone, Giandomenico (Journal of Public Governance, 2015)
Since the late 1970s European governments have been forced to change their traditional modes of governance in response to such trends as increasing international competition and deepening economic and monetary integration within the European Union. Strategic adaptation to the new realities has resulted in a reduced role for the positive, interventionist state and a corresponding increase in the role of the regulatory state: rule making is replacing taxing and spending. The paper’s first part identifies three sets of strategies leading to the growth of the regulatory state as external or market regulator, and as internal regulator of decentralised administration. The second part examines major structural changes induced by changes in regulatory strategies. The institutional and intellectual legacy of the interventionist state is a major impediment to the speedy adjustment of governance structures to new strategies. It would be unwise to underestimate the difficulties of the transition from the positive to the regulatory state, but it is important to realise that international competition takes place not only among producers of goods and services but also, increasingly, among regulatory regimes. Regulatory competition will reward regimes in which institutional innovations do not lag far behind the new strategic choices.